Spontaneous pneumothorax: time to rethink management?. Issue 7 (July 2015) - Bintcliffe, Oliver J; Hallifax, Rob J; Edey, Anthony; Feller-Kopman, David; Lee, Y C Gary; Marquette, Charles H; Tschopp, Jean-Marie; West, Douglas; Rahman, Najib M; Maskell, Nick A
Summary There are substantial differences in international guidelines for the management of pneumothorax and much geographical variation in clinical practice. These discrepancies have, in part, been driven by a paucity of high-quality evidence. Advances in diagnostic techniques have increasingly allowed the identification of lung abnormalities in patients previously labelled as having primary spontaneous pneumothorax, a group in whom recommended management differs from those with clinically apparent lung disease. Pathophysiological mechanisms underlying pneumothorax are now better understood and this may have implications for clinical management. Risk stratification of patients at baseline could help to identify subgroups at higher risk of recurrent pneumothorax who would benefit from early intervention to prevent recurrence. Further research into the roles of conservative management, Heimlich valves, digital air-leak monitoring, and pleurodesis at first presentation might lead to an increase in their use in the future.